Petrological constraints on melt generation beneath the Asal Rift (Djibouti) using quaternary basalts. (22nd August 2013) - Pinzuti, Paul; Humler, Eric; Manighetti, Isabelle; Gaudemer, Yves
Abstract : [1] The temporal evolution of the mantle melting processes in the Asal Rift is evaluated from the chemical composition of 56 new lava flows sampled along 10 km of the rift axis and 9 km off‐axis (i.e., erupted within the last 620 kyr). Petrological and primary geochemical results show that most of the samples of the inner floor of the Asal Rift are affected by plagioclase accumulation. Trace element ratios and major element compositions corrected for mineral accumulation and crystallization show a symmetric pattern relative to the rift axis and preserved a clear signal of mantle melting depth variations. While FeO, Fe8.0, Zr/Y, and (Dy/Yb)N decrease from the rift shoulders to the rift axis, SiO2, Na/Ti, Lu/Hf increase and Na2 O and Na8.0 are constant across the rift. These variations are qualitatively consistent with shallow melting beneath the rift axis and deeper melting for off‐axis lava flows. Na8.0 and Fe8.0 contents show that beneath the rift axis, melting paths are shallow, from 81 ± 4 to 43 ± 5 km. These melting paths are consistent with adiabatic melting in normal‐temperature fertile asthenosphere, beneath an extensively thinned mantle lithosphere. On the contrary, melting on the rift shoulders (from 107 ± 7 to 67 ± 8 km) occurred beneath thicker lithosphere, requiring a mantle solidus temperature 100 ± 40°C hotter. In this geodynamic environment, the calculated rate of lithospheric thinning appears to be 4.0 ± 2.0 cm yr −1, a value close to the mean spreading rate (2.9 ± 0.2 cm yr −1 ) over the last 620 kyr. Key Points: Melt generation during rifting process Correction for mineral accumulation Lithospheric thickness and thinning rate